Anterior Segment Optical Coherence Tomography Angiography Imaging of Conjunctiva and Intrasclera in Treated Primary Open-Angle Glaucoma - Akagi, Tadamichi; Uji, Akihito; Okamoto, Yoko; Suda, Kenji; Kameda, Takanori; Nakanishi, Hideo; Ikeda, Hanako Ohashi; Miyake, Masahiro; Nakano, Eri; Motozawa, Naohiro; Tsujikawa, Akitaka (American journal of ophthalmology, 2019)
To investigate conjunctival and intrascleral vasculature in glaucoma eyes using anterior segment (AS)-optical coherence tomography angiography (OCTA) and assess the factors contributing to the vessel density in AS-OCTA images. Prospective, cross-sectional study. Thirty-four patients with primary open-angle glaucoma and 20 healthy subjects were included. A swept-source OCT system was used to obtain the AS-OCTA images of the corneoscleral limbus at the nasal and temporal quadrants. Vessel densities were measured in the superficial (from the conjunctival epithelium to a depth of 200 μm) and deep (from a depth of 200 to 1000 μm) layers. The vessel density was compared between healthy and glaucoma eyes, and the associations of the vessel density with possible confounding factors were analyzed using univariable and multivariable analyses. The vessel density was not significantly different between healthy eyes and eyes with glaucoma. There was a significant association of superficial vessel density with the use of a prostaglandin analog (P = .007) and with nasal location (P = .016) in eyes with glaucoma. Deep vessel density was significantly smaller with advancing age (P = .029) in healthy eyes and greater with higher intraocular pressure (P = .021) in eyes with treated glaucoma. AS-OCTA images may be useful for the objective assessment of conjunctival hyperemia and helpful for understanding the pathophysiology of post-trabecular aqueous humor outflow.